Effect of Covid-19 on Mental Health of Adolescents in Malawi (Policy Brief) - Kainja, Jimmy; M'manga, Chilungamo; Maliwichi, Limbika; Kondowe, Fiskani; Nyamali, Simunye; Mchenga, Martina; Ndasauka, Yamikani (My University, 2024)
COVID-19 has profoundly affected life as COVID-19 measures requiring social isolation, movement restrictions, and economic shutdowns change the psychosocial environment worldwide. These measures can significantly threaten the mental health of children and adolescents, especially as the closure of schools meant minimal social contact and out-of-home leisure activities for adolescents. School routines are essential coping mechanisms for young people with mental health issues. When schools are closed, they lose an anchor in life, and their symptoms could relapse. Although others turned to home school with the support of their parents, the challenge was that parents were also required to work from home. The COVID-19 mitigating measures mean the absence of external support by other family members, and social support systems have fallen away. Besides worry and anxiety related to COVID-19, the economic situation has worsened with high and rising levels of unemployment worldwide. These factors have put much pressure on children, adolescents and their families, resulting in distress, mental health problems and violence. For some children with depression, there will be considerable difficulties adjusting to everyday life when school resumes. (Lancet, 2020). The Covid-19 and Mental Health in Malawi project conducted a study to assess the effects of Covid-19 on adolescents' mental health in the country. Specifically, the study looked at Covid-19-related depression, anxiety and Post-Traumatic Stress Disorder (PTSD). The study used quantitative and qualitative methods. It collected quantitative data through a survey (n=320) and qualitative data through focus group discussions (n-4), and key informant interviews (n=12) with guardians and caregivers of adolescents in Malawi. The data were collected from four districts: Blantyre, Mangochi, Lilongwe and Karonga.
Keywords: COVID-19; Malawi; Mental Health; Adolescents